Andean Lima. Searching for the Andean musical traces in Lima (1880-1930) - Rohner, Fred (2018)
On the basis of a set of musical and sound tracks, the following article aims to discuss if Lima was Andean before the migratory processes of the mid-twentieth century. It looks for the existence of musical evidences that would reveal a set of Andean traces in the Peruvian capital before the modern migration. Therefore, it seeks to understand the place of musical and performative genres, such as the yaraví and the danza de las pallas, in the cultural constructions that have been drawing Lima as a city detached from the Andean culture.